The prognostic value of advanced lung cancer inflammation index (ALI) in elderly patients with heart failure - Yuan, Xiao; Huang, Bi; Wang, Ruiyu; Tie, Hongtao; Luo, Suxin (Frontiers in Cardiovascular Medicine, 2022)
Purpose: The advanced lung cancer inflammation index (ALI) is a novel inflammatory and nutritional index that exerts prognostic value in various types of cancer. A previous study demonstrated that ALI at discharge could predict the prognosis in patients with acute decompensated heart failure (ADHF). However, the long-term prognostic value of ALI on admission in elderly heart failure (HF) inpatients remains unclear. Methods: We retrospectively collected HF inpatients over 65-year-old who hospitalized in our cardiology center during the whole year of 2015. ALI was calculated as body mass index (BMI) × serum albumin (Alb)/neutrophil-to-lymphocyte ratio (NLR). Patients were divided into two groups by the optimal cutoff value of ALI for predicting all-cause mortality using time-dependent receiver operating characteristic (ROC) curves. The Spearman rank correlation coefficient was computed to evaluate the correlation between ALI and the geriatric nutritional risk index (GNRI). Kaplan-Meier curves, Cox survival analyses, time-dependent ROC analyses, and net reclassification improvement (NRI) analyses were used to assess the prognostic effect of ALI on all-cause mortality and cardiovascular mortality. Results: Over a 28-month median follow-up, all-cause and cardiovascular mortality occurred in 192 (35.4%) and 132 (24.3%) out of 543 patients, respectively. The optimal cutoff value of ALI for predicting all-cause mortality at two years was 25.8. Spearman’s correlation coefficient showed a moderate positive linear correlation between ALI and GNRI (r=0.44, p < 0.001). The Kaplan–Meier analysis revealed that the cumulative incidences of both all-cause and cardiovascular mortalities were significantly higher in patients with lower ALI. The multivariate Cox proportional hazard analyses indicated that ALI was an independent predictor for both all-cause mortality and cardiovascular mortality. Time-dependent ROC analyses showed that ALI was comparable to GNRI in predicting long-term all-cause mortality and cardiovascular mortality at two years. However, the estimated NRI indicated that the addition of ALI could not significantly improve risk stratification of base models for all-cause mortality or cardiovascular mortality. Conclusion: Higher ALI was significantly associated with lower all-cause and cardiovascular mortalities in elderly HF patients. ALI on admission could be a competent nutrition-inflammation marker with independent predictive value for evaluating the long-term mortality of HF in elder population.